Experimental determination of the Ag L -subshell x-ray-production cross sections by electron impact through two bulk target methods - Rodríguez, Tabatha P.; Sepúlveda, Andrés H.; Pérez, Pablo Daniel; Trincavelli, Jorge Carlos; Castellano, Gustavo Eugenio (American Physical Society, 2023)
Fil: Rodríguez, Tabatha P.. Universidad Tecnológica Metropolitana; Chile